Pengaruh Konsumsi Rumah Tangga, Investasi, dan Net Ekspor Terhadap Indeks Pembangunan Manusia di Indonesia periode tahun 2018-2022 - Alya Hafizhatul Husni; Amar, Syamsul (Universitas Negeri Padang, 2024)
This study aims to analyze the impact of: (1) household consumption, (2) investment, (3) net exports, and (4) the combined effect of household consumption, investment, and net exports on the human development index (HDI) in Indonesia. This research adopts a quantitative approach using secondary data in the form of panel data, which integrates time series data from 2018 to 2022 with cross-sectional data from 34 provinces across Indonesia. The analysis method employed is panel data analysis. The findings indicate that: (1) household consumption has an insignificant effect on the HDI in Indonesia, while (2) investment and (3) net exports exhibit a significant positive impact on the HDI